2004
DOI: 10.1002/ls.3010160208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MoDDP on the antioxidative properties of ZnDDP in mineral oil

Abstract: The antioxidative actions of zinc and molybdenum dithiophosphates and their mixtures were evaluated using the RBOT (rotary bomb oxidation test) and the ISOT (Indiana stirring oxidation test). The results showed a synergistic effect on the antioxidative action with certain mixtures of the additives in mineral oil. FTIR spectra indicated the presence of some oxidation products and the degradation of the additives in the additive-containing oils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Molybdenum dialkyldithiophosphate (MoDDP) is a typical friction modifier which is often used in many industrial and automotive applications to reduce frictional energy losses [4]. A lot of experimental results have shown that it can reduce friction and increase durability of metal surfaces by forming a tribofilm [5][6][7][8][9][10][11]. Previous results have demonstrated that MoDDP reaction films could produce low friction coefficient (less than 0.05) after a few running cycles [8].…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum dialkyldithiophosphate (MoDDP) is a typical friction modifier which is often used in many industrial and automotive applications to reduce frictional energy losses [4]. A lot of experimental results have shown that it can reduce friction and increase durability of metal surfaces by forming a tribofilm [5][6][7][8][9][10][11]. Previous results have demonstrated that MoDDP reaction films could produce low friction coefficient (less than 0.05) after a few running cycles [8].…”
Section: Introductionmentioning
confidence: 99%